A −60 °C Low‐Temperature Aqueous Lithium Ion‐Bromine Battery with High Power Density Enabled by Electrolyte Design. Issue 25 (18th May 2022) - Wang, Mingtan; Li, Tianyu; Yin, Yanbin; Yan, Jingwang; Zhang, Huamin; Li, Xianfeng
Abstract: Aqueous lithium‐ion batteries are normally limited at low temperatures, because of the consequent low conductivity of electrolytes and the sluggish kinetics of electrode materials. Herein, a high‐performance ultra‐low temperature aqueous lithium ion‐bromine battery (ALBB) realized by a tailored functionalized electrolyte (TFE) consisting of lithium bromide and tetrapropylammonium bromide (TPABr) is reported, which can maintain liquid state with high conductivity (1.89 mS cm ‐1 ) at − 60 ° C. In addition, with the help of excellent bromine‐fixation of TPABr, the high reversible capacity can be provided by the fast redox reaction of Br2 /Br ‐ couple in the cathode from room temperature (RT) to − 60 ° C. Moreover, 1, 4, 5, 8‐naphthalenetetracarboxylic dianhydride‐derived polyimide anode can deliver excellent low‐temperature capacity retention as well as enhanced rate capability and reversibility at RT in TFE. As a result, the designed TFE can endow ALBB with high energy densities (98, 64, and 32 Wh kgdry ‐1 at RT, − 40, and − 60 ° C, respectively), outstanding power densities (24.6 and 1.2 kW kgdry ‐1 at RT and − 40 ° C, respectively), and superior capacity retentions (94% and 98% after running 1000 cycles at RT and − 40 ° C, respectively). This work demonstrates a novel strategy to widen the temperature range of aqueous batteries. Abstract : A novel ultra‐low temperature aqueous lithium ion‐bromine battery (ALBB) realized by a tailored functionalized electrolyte (TFE) with high conductivity (1.89 mS cm –1 ) at −60 °C, consisting of LiBr and tetrapropylammonium bromide, is designed. The TFE endows the ALBB with high energy density, outstanding power density, and superior capacity retention at both room and low temperatures.